The Role of Fiqh Teachers in Improving Discipline in Congregational Prayers for Santri in the New Normal Era - Ruslan, Wahidah; Juddah, Abu Bakar (IAIN Parepare, 2021)
This study aims to determine the performance of congregational prayers for santri to improve discipline in Pesantren DDI As-Salman Allakuang, Kabupaten Sidrap. This research uses qualitative research that is inductive in nature with data collection methods, namely observation, interviews and documentation. The location was taken place of research in Pesantren DDI As-Salman Allakuang. These results indicate, 1) the implementation of the prayer with students of Pesantren DDI As-Salman Allakuang during the new normal period did not go well because there were still some students who did not perform their prayers in congregation on time, 2) the role of the fiqh teacher in fostering disciplined prayer in congregation with students in Pesantren DDI As-Salman Allakuang has been very good because the fiqh teacher has given advice and encouragement by teaching the privileges of people who pray in congregation and implementing strategies in improving disciplinary attitudes to students, namely cooperative, affective, exemplary learning strategies and giving sanctions and punishments.